2018
DOI: 10.18203/2349-2902.isj20180835
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of the incidence and disability caused by mesh neuralgia after inguinal mesh hernioplasty and the effects of prophylactic ilioinguinal neurectomy and its role in preventing chronic groin pain after inguinal hernioplasty

Abstract: Background: Residual neuralgia, called as Inguinodynia, is an important complication unique to groin hernia repair. The reported incidence ranges between 9-63%. The symptoms are potentially disabling. Symptoms are often more pronounced on axial twisting of body. Methods for prevention include identification and preservation of all nerves, Ilioinguinal Neurectomy and triple Neurectomy during surgery.Methods: One hundred patients underwent elective unilateral Lichtenstein’s tension free hernioplasty. 50 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…20 Also, Sunkar et al reported that significantly fewer patients had pain after coughing 5 times at 6 months, in the neurectomy group as compared with the nonneurectomy group (p value<0.0001). 18 In the present study, after 1 month follows up, pain during vigorous activity was noted in 48.9% of patients in the neurectomy group (A), while it was noted in 55.6% of patients in the nerve preservation group (B). But after 6 months follow up, 16 patients (35.6%) were still experiencing pain in the nerve preservation group whereas, only 6 patients (13.3%) in the neurectomy group were still complaining of pain (p value=0.005) (significant).…”
Section: Discussionsupporting
confidence: 42%
See 3 more Smart Citations
“…20 Also, Sunkar et al reported that significantly fewer patients had pain after coughing 5 times at 6 months, in the neurectomy group as compared with the nonneurectomy group (p value<0.0001). 18 In the present study, after 1 month follows up, pain during vigorous activity was noted in 48.9% of patients in the neurectomy group (A), while it was noted in 55.6% of patients in the nerve preservation group (B). But after 6 months follow up, 16 patients (35.6%) were still experiencing pain in the nerve preservation group whereas, only 6 patients (13.3%) in the neurectomy group were still complaining of pain (p value=0.005) (significant).…”
Section: Discussionsupporting
confidence: 42%
“…17 Sunkar et al reported that 8% of his patients aged between 15-30 years and 34% aged between 61and 75 years old. 18 Saravanan et al reported that most of his patients aged between 31 to 40 years in both groups followed by 41 to 50 years. 19 In the present study, the right oblique hernia was the commonest and represented 40% in the neurectomy group and 42.2% in the nerve preservation group.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…4 There is a symptom complex of neuropathic and nonneuropathic pain. The neuropathic causes include inadvertent entrapment of nerve in suture or mesh, perineural fibrosis, partial division, crushing of nerve, or diathermy burns, 2,3 triggered by hyperextension of the hip and walking. The non-neuropathic pain is actually somatic pain due to periosteal reaction, scar tissue, mechanical pressure caused by folded mesh called 'meshoma' and visceral pain, which is experienced during ejaculation.…”
Section: Introductionmentioning
confidence: 99%